2012
DOI: 10.4161/viru.18685
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of cryptococcal meningitis

Abstract: Fungal meningitis is a serious disease caused by a fungal infection of the central nervous system (CNS) mostly in individuals with immune system deficiencies. Fungal meningitis is often fatal without proper treatment, and the mortality rate remains unacceptably high even with antifungal drug interventions. Currently, cryptococcal meningitis is the most common fungal meningitis in HIV-1/AIDS, and its disease mechanism has been extensively studied. The key steps for fungi to infect brain and cause meningitis aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
94
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 109 publications
2
94
0
3
Order By: Relevance
“…The molecular basis of cryptococcal infection of the CNS is an area of intensive investigation. Multiple fungal and host factors have been identified to play a role in the fungal penetration of the blood brain barrier (BBB) and to cause CNS infection [2][3][4][5]. The polysaccharide capsule of C. neoformans is a major virulence factor that is associated with the outcome following initial pathogen-host interaction, including BBB crossing and establishing CNS infection [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The molecular basis of cryptococcal infection of the CNS is an area of intensive investigation. Multiple fungal and host factors have been identified to play a role in the fungal penetration of the blood brain barrier (BBB) and to cause CNS infection [2][3][4][5]. The polysaccharide capsule of C. neoformans is a major virulence factor that is associated with the outcome following initial pathogen-host interaction, including BBB crossing and establishing CNS infection [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…ryptococcus neoformans, an invasive opportunistic pathogen of the central nervous system, is the most frequent cause of fungal meningitis, resulting in more than 625,000 deaths per year worldwide (1,2). Exposure to C. neoformans is common, as it is an environmental fungus found in the soil and can enter the lungs through inhalation, leading to pulmonary infection.…”
mentioning
confidence: 99%
“…Clinical observations and experimental data have shown that uncontrolled infection of the respiratory tract precedes the development of disseminated infection and/or meningitis. The mechanisms by which C. neoformans reaches and actually enters the brain following its escape from the lung are complex and not fully understood; these include intravascular trapping followed by paracellular or transcellular migration or transmigration within circulating phagocytes (56). The data presented here suggest that Cnes2 restricts progressive infection by enhancing the pulmonary The expression of classical (Nos2) and alternative (Arg1 and Fizz1) activation markers by total adherent pulmonary macrophages was evaluated by qRT-PCR at 14 dpi.…”
Section: Discussionmentioning
confidence: 99%